1996
DOI: 10.1097/00000542-199609000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Target-Controlled Infusion of Propofol-Sufentanil or Sufentanil-Midazolam for Coronary Artery Bypass Graft Surgery

Abstract: Target-controlled infusions of propofol or sufentanil, supplemented by infusions of sufentanil or midazolam, respectively, were suitable to provide anesthesia for coronary artery bypass graft surgery. Continuous monitoring revealed a high prevalence of hemodynamic abnormalities. Despite greater hypotension in the propofol-sufentanil group and greater hypertension in the sufentanil-midazolam group, episodes of myocardial ischemia were similar for both groups and were not temporally related to episodes of hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The effect site concentration of sufentanil used in the present study (0.4±0.6 ng mL À1 ) is consistent with what is called`low-dose' sufentanil regimen during cardiac surgery [17]. The average total dose of sufentanil was 2.7 mg kg À1 in the present study which is comparable to that reported by Jain and his colleagues in the`low dose' sufentanil group (2.4 0.8 mg kg À1 ) [17].…”
Section: Clinical Relevance Of the Anaesthetic Regimen Usedsupporting
confidence: 91%
See 2 more Smart Citations
“…The effect site concentration of sufentanil used in the present study (0.4±0.6 ng mL À1 ) is consistent with what is called`low-dose' sufentanil regimen during cardiac surgery [17]. The average total dose of sufentanil was 2.7 mg kg À1 in the present study which is comparable to that reported by Jain and his colleagues in the`low dose' sufentanil group (2.4 0.8 mg kg À1 ) [17].…”
Section: Clinical Relevance Of the Anaesthetic Regimen Usedsupporting
confidence: 91%
“…The average total dose of sufentanil was 2.7 mg kg À1 in the present study which is comparable to that reported by Jain and his colleagues in the`low dose' sufentanil group (2.4 0.8 mg kg À1 ) [17]. The average total dose of propofol in the present study was 17 mg kg À1 , which is approximately half of that reported by Jain et al (32.6 11.9 mg kg À1 ) [17]. Simulation of predicted propofol concentrations, despite obvious methodological limitations, resulted in predicted average effect site propofol concentrations between 2.7 and 3.4 mg mL À1 (range 2±5 mg mL À1 ).…”
Section: Clinical Relevance Of the Anaesthetic Regimen Usedsupporting
confidence: 89%
See 1 more Smart Citation
“…Target‐controlled infusions with propofol have been used in human patients for a wide range of procedures, from dental work under sedation (Oei‐Lim and others 1998) to cardiac surgery (Barvais and others 1996, Jain and others 1996). The technique has also been used for conscious sedation during endoscopy (Church and others 1991) and in the intensive care unit (Snellen and others 1990).…”
mentioning
confidence: 99%
“…A regimen of TCI sufentanil supplemented with midazolam has been compared with TCI propofol supplemented with sufentanil in patients undergoing cardiac surgery [8]. Outcome in both groups was similar, although there was more hypotension in the propofol-sufentanil group and more hypertension in the sufentanil-midazolam group.…”
Section: Intra-operative Analgesiamentioning
confidence: 99%